Comparisons of Efficacy of Intravitreal Aflibercept and Ranibizumab in Eyes with Diabetic Macular Edema. (3rd July 2017) - Shimizu, Norihiro; Oshitari, Toshiyuki; Tatsumi, Tomoaki; Takatsuna, Yoko; Arai, Miyuki; Sato, Eiju; Baba, Takayuki; Yamamoto, Shuichi
Abstract : We compared the efficacy of intravitreal aflibercept (IVA) to intravitreal ranibizumab (IVR) injections in eyes with diabetic macular edema (DME). The medical records of 49 eyes of 36 patients who were diagnosed with DME and had received IVR and 46 eyes of 40 patients who had received IVA treatment were reviewed. The central macular thickness (CMT) and best-corrected visual acuity (BCVA) were measured at the baseline and at 1, 3, and 6 months after the IVR or IVA. The mean number of injections of IVR was 2.6 ± 1.1 and of IVA was 2.7 ± 1.4 . At 6 months, the CMT was significantly thinner than the baseline after IVR and after IVA. The mean BCVA was significantly better than the baseline after IVR only at 1 and 3 months and after IVA at 1 and 6 months. The BCVA of eyes with serous retinal detachment (SRD) was significantly better at 1 month after the IVR and at 1 month and 6 months after the IVA. The BCVAs improved more significantly in the SRD+ group than in the SRD− group. The effects of IVA persist longer than that of IVR. The effectiveness of both IVR and IVA was not dependent on the presence of SRD (IRB#2107).